Faktor yang Berhubungan dengan Penggunaan Partograf dalam Persalinan oleh Bidan Praktik Mandiri: Determinants of Partograph Use in Childbirth by Independent Practice Midwives - Silfia, Niluh Nita (Jurnal Bidan Cerdas, 2020)
Partographs are guidelines for childbirth observations that will facilitate labor assistants in first identifying emergency cases and complications for mothers and fetuses. Preliminary survey at the Sigi Community Health Sub-Center (Pustu) of the 8 Pustu midwives found two midwives (25%) to complete a complete partograph, six midwives (75%) incomplete. The purpose of this study was to determine the determinant factors associated with the use of partographs in labor. The design of this study used observational analytic methods with a cross-sectional approach. 24 BPM survey results were obtained with 30 samples of midwives who met the research criteria and data completeness. The sampling technique was by the total population. Data analysis used logistic regression. The multivariate analysis results showed that APN training was the most influential factor in the use of partographs in labor by midwives. Statistical test results obtained a POR value of 37.7 (95% CI 12.1 - 60.2). This study suggests that midwives must have APN certificates to be valid in providing services.